The Influence of Brand Image, Location, and Word of Mouth on the Purchase Decision of Honda Motorcycles with eSAF Frame at TDM Honda Nanga Pinoh - Naufal Dwi Fahreza; Helman Fachri (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to determine the influence of brand image, location, and word of mouth on the purchase decision of Honda motorcycles with eSAF frames at TDM Nanga Pinoh City. This research uses an associative method. The sample in this study consists of 100 respondents who are both users and consumers of Honda motorcycles with eSAF frames, using purposive sampling techniques. The instrument testing techniques in this study use validity tests, reliability tests, classical assumption tests using normality tests, linearity tests, multicollinearity tests, and hypothesis testing using multiple linear regression tests, correlation coefficient tests, coefficient of determination tests, simultaneous tests, and partial tests. The data analysis results show that the multiple linear regression model produces the equation Y = 1.341 + 0.150X₁ + 0.208X₂ + 0.252X₃. The correlation coefficient (R) value of 0.740 indicates that the relationship between the three independent variables and purchasing decisions is in the strong category. The coefficient of determination (R²) of 0.547 shows that the three independent variables are able to explain 54.7% of the variation in the purchasing decision of Honda motorcycles with eSAF frames, while the remaining 45.3% is explained by other factors outside this research model. Based on the individual test (t-test), it was found that the variables Brand Image (X1), Location (X2), and Word of Mouth (X3) each have a positive influence on the Purchase Decision (Y) variable. The simultaneous test results (F-test) prove that the three independent variables have a positive and significant influence on purchasing decisions. Future research is suggested to examine other factors such as digital promotion, consumer trust, or service quality to deepen understanding of what influences purchasing decisions.